Analisis Pengaruh Literasi Digital Terhadap Pola Konsumsi Masyarakat Di Era E-Commerce - Putri Salsabila; Maimunah Maimunah; Reni Ria Armayani Hasibuan (Indo Publishing, 2026)
The development of information and communication technology has driven changes in consumer consumption patterns through the increasingly widespread use of e-commerce platforms. Ease of access to information, digital transactions, and various promotional strategies offered by marketplaces provide benefits to consumers, but also have the potential to increase consumer behavior. Therefore, digital literacy is a crucial factor that can help people make more rational and responsible consumption decisions. This study aims to analyze the influence of digital literacy on consumer consumption patterns in the e-commerce era. The method used was qualitative research with a library research approach. Data were obtained from scientific journals, books, research articles, and the Indonesian Digital Literacy infographic published by the Ministry of Communication and Digital. Data analysis was conducted using descriptive qualitative methods, examining the relationship between digital literacy and consumer behavior. The results show that digital literacy has a significant influence on consumer consumption patterns. Individuals with high levels of digital literacy tend to be more critical in evaluating information, able to distinguish between needs and wants, and more discerning in dealing with various digital promotions. Therefore, increasing digital literacy can be one way to reduce consumer behavior while creating more rational, productive, and sustainable consumption patterns in the digital economy era.